L’eco del pensiero rosacrociano nell’idea di teatro tedesco del secondo Settecento - Bellavia, Sonia (Filosofia, 2021)
German Rosicrucianism, as Frances Yates notes in her famous studies, was a historically recognizable style of thought at the beginning of the 17th century, that had its origins in the scientific, mystical and poetic aspirations of the Elizabethan age. As an anti-Catholic movement, opposed by the Jesuits, it was short-lived, but it transmitted to the 18th century its theoretical legacy, which included the idea of the centrality of theatre. In light of this, the radical renewal of theatre that took place in the German-speaking world, starting with Lessing’s departure from the French Aristotelian model and making Shakespeare and Nature its banner, can be considered differently, as not in contrast to traditional theatrical historiography.